Mediación policial como herramienta para la resolución de conflictos - Sandoval Cruz, Estefanía
This article will present the results of the complementary training in Peace Manager for the police members of the city of Montería, which the CGA Administrative Management Center created based on four key competences that provide tools to solve in the faster and best possible way the situations of conflict that can arise in daily coexistence, avoiding in this way to end in long and painful criminal and administrative proceedings.The type of research is qualitative - descriptive and the techniques of data collection used were observation and a questionnaire that was able to identify the characteristics of the police trainees, worked by different pedagogical strategies that allowed to be molded and oriented to promote peace within a community.According to the impact generated in Monteria and evinced by the citizens, the different entities that are committed to building a true peace are urged to implement this training at a national level, mainly the National Police of Colombia based on the new Police Code, where mediation takes force as a preventive action in the community.